2020
DOI: 10.3389/fcimb.2020.00370
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia spp. Yeasts of Emerging Concern in Fungemia

Abstract: Malassezia spp. are lipid-dependent yeasts, inhabiting the skin and mucosa of humans and animals. They are involved in a variety of skin disorders in humans and animals and may cause bloodstream infections in severely immunocompromised patients. Despite a tremendous increase in scientific knowledge of these yeasts during the last two decades, the epidemiology of Malassezia spp. related to fungemia remains largely underestimated most likely due to the difficulty in the isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 135 publications
(243 reference statements)
0
95
0
Order By: Relevance
“…As the standard culture media in most clinics do not include lipid supplementation, the role of Malassezia in BSIs is likely underestimated (Rhimi et al . 2020 ; Chen et al . 2020 ; Theelen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the standard culture media in most clinics do not include lipid supplementation, the role of Malassezia in BSIs is likely underestimated (Rhimi et al . 2020 ; Chen et al . 2020 ; Theelen et al .…”
Section: Introductionmentioning
confidence: 99%
“…2018 ; Saunte, Gaitanis and Hay 2020 ), and is the most frequently observed causative species (Rhimi et al . 2020 ) in Malassezia BSI. Amplified fragment length polymorphism (AFLP) analyses indicated that the species is genetically heterogenous and implies the presence of multiple physiologically diverse strains.…”
Section: Introductionmentioning
confidence: 99%
“…Under certain circumstances (e.g., increased humidity and temperature), these yeasts cause common human skin diseases, including pityriasis versicolor, seborrheic dermatitis and folliculitis [2]. They can also cause severe bloodstream infections in neonates or immunocompromised patients hospitalized in intensive care with lipidic parenteral nutrition [3][4][5][6]. Their role in atopic dermatitis and psoriasis was also reported [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Malassezia are basidiomycetous yeasts that are the dominant fungal component of the healthy human skin microbiome (1,2). Nevertheless, they can also take on pathogenic roles in various skin disorders, and have been implicated in cases of infection associated with several comorbidities (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Non-culture based sequencing methods revealed Malassezia presence in other ecological niches, including insects, nematodes, corals, sponges, deep-sea environments, and soils (13)(14)(15), suggesting that Malassezia are ecologically diverse.…”
Section: Introduction (573 Words)mentioning
confidence: 99%